Evaluation of the efficacy of Saccharomyces cerevisiae cell wall to ameliorate the toxic effects of aflatoxin in broilers - Santin, Elizabeth; Carlos Paulillo, Antonio [UNESP]; Maiorka, Alex; Okada Nakaghi, Laura Satiko [UNESP]; Macari, Marcos [UNESP]; da Silva, Ana Vitória Fischer; Carlos Alessi, Antonio [UNESP] (My University, 2003)
A study was carried out to evaluate the efficacy of Saccharomyces cerevisiae (SC) as an inhibitor of aflatoxicosis in broilers. Clinic, pathologic, immune and productive aspects of broilers fed with aflatoxin in the diets were studied. The results showed that the feed intake and weight gain were negatively affected (P < 0.01) for aflatoxin in diet (1000 ppb). The SC (0, 20%) added to diet did not ameliorated the negatively aflatoxin effect at broiler weight gain, however the SC improve the feed conversion in this birds. The humoral immune response of broilers vaccinated against Newcastle virus disease (NDV) was reduced for aflatoxin in diet, as also the liver, kidneys and bursa of Fabricius were negatively affected for this toxin at diet. The SC did not improve the hemagglutination inhibiting antibody titers in birds fed with aflatoxin in diet, however improve the immune response of broilers at challenge with strain velogenic of NDV. © Asian Network for Scientific Information 2003.
Keywords: Aflatoxicosis; Broilers; Cellular wall S; Cerevisiae; Immune response